Psychophysical Precision in the Total Act - Lidia Olinto; Matteo Bonfitto (Revista Brasileira de Estudos da Presença, 2013)
The Constant Prince, an internationally famous play directed by J. Grotowski, in which R. Cieslak’s acting stood out remarkably, presents some peculiarities related to the notion of scenic precision and, based on this premise, this paper proposes to describe and discuss them. The goal of this paper is to explore how in this play, in which two different acting techniques were used, there are differences related to the way the actors mobilize and control their psychic and physical resources. Using genetic analysis, the paper’s intention is also to point out why only the acting performance of Cieslak was considered a Total Act by Grotowski.